2013
DOI: 10.1099/ijs.0.050468-0
|View full text |Cite
|
Sign up to set email alerts
|

A thermophilic, hydrogenogenic and carboxydotrophic bacterium, Calderihabitans maritimus gen. nov., sp. nov., from a marine sediment core of an undersea caldera

Abstract: A hydrogenogenic, carboxydotrophic marine bacterium, strain KKC1T, was isolated from a sediment core sample taken from a submerged marine caldera. Cells were non-motile, Gram-stain-negative, 1.0–3.0 µm straight rods, often observed with round endospores. Strain KKC1T grew at 55–68 °C, pH 5.2–9.2 and 0.8–14 % (w/v) salinity. Optimum growth occurred at 65 °C, pH 7.0–7.5 and 2.46 % salinity with a doubling time of 3.7 h. The isolate grew chemolithotrophically, producing H2 from carbon monoxide (CO) oxidation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…As reported previously, the C. maritimus KKC1 is most closely related to Moorella species on the basis of 16S rRNA phylogenetic analysis (23) (Fig. 1A).…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…As reported previously, the C. maritimus KKC1 is most closely related to Moorella species on the basis of 16S rRNA phylogenetic analysis (23) (Fig. 1A).…”
Section: Resultssupporting
confidence: 53%
“…maritimus KKC1 can grow heterotrophically on pyruvate, lactate, fumarate, glucose, fructose, and mannose with thiosulfate as an electron acceptor under an N 2 atmosphere (23). Metabolic pathways predicted by Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that the C. maritimus KKC1 genome encoded a complete glycolytic pathway and an incomplete tricarboxylic acid (TCA) cycle that lacked citrate synthase (present in Moorella species) and malate dehydrogenase (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations